Using the training method and its impact on learning some new skills (Journal of the College of Basic Education, 2022)
The researchers used the training method, which is one of (Mosten's) methods, to identify its effect on learners and to provide appropriate learning opportunities through the optimal investment of effort and time. In this method, some offensive basketball skills were learned for intermediate school students in Baghdad.The research aims to:1- Preparing a curriculum using the training method to learn some offensive skills in basketball at the ages of (13-14) years.2- Identifying the effect of the curriculum using the training method in learning some offensive skills in basketball at the ages of (13-14) years.